2010
DOI: 10.1161/circresaha.109.205385
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Angiotensin II Type 1 Receptor–Mediated Upregulation of Calcineurin Activity Underlies Impairment of Cardioprotective Signaling in Diabetic Hearts

Abstract: Rationale: The diabetic heart is resistant to ischemic preconditioning because of diabetes-associated impairment of phosphatidylinositol 3-kinase (PI3K)-Akt signaling. The mechanism by which PI3K-Akt signaling is impaired by diabetes remains unclear. Objective: Here, we examined the hypothesis that phosphorylation of iabetes mellitus not only accelerates atherosclerosis of the coronary artery but also induces functional and structural abnormalities in the myocardium. In addition, recent studies have shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 14 publications
9
64
1
Order By: Relevance
“…The plasma glucose level was significantly higher in OLETF rats than in LETO rats (286.4 Ϯ 10.5 vs. 118.2 Ϯ 4.2 mg/dl, P Ͻ 0.05), confirming an obese T2DM phenotype in OLETF rats. The results were consistent with the results of our previous studies (7,17,35) showing hyperinsulinemia, insulin resistance, and hypertriglyceridemia in OLETF rats at the same age.…”
Section: Resultssupporting
confidence: 93%
“…The plasma glucose level was significantly higher in OLETF rats than in LETO rats (286.4 Ϯ 10.5 vs. 118.2 Ϯ 4.2 mg/dl, P Ͻ 0.05), confirming an obese T2DM phenotype in OLETF rats. The results were consistent with the results of our previous studies (7,17,35) showing hyperinsulinemia, insulin resistance, and hypertriglyceridemia in OLETF rats at the same age.…”
Section: Resultssupporting
confidence: 93%
“…The majority of preclinical experimental studies investigating the effect of diabetes on the myocardial response to either ischemic or pharmacologic preconditioning has found that the presence of diabetes renders the heart more resistant to the infarct size-limiting effects of preconditioning (reviewed in Ferdinandy et al, 2007;Miki et al, 2012). Recent experimental studies have also shown that the cardioprotective efficacy of pharmacologic preconditioning using a variety of different agents, including erythropoietin (Miki et al, 2009;Hotta et al, 2010), d-opioid receptor agonist (Hotta et al, 2010), isoflurane (Matsumoto et al, 2009), L-glutamate (Povlsen et al, 2009), remifentanil , and helium (Huhn et al, 2009b), is also impaired in the diabetic heart. Whittington et al (2013b) investigated the combined effect of diabetes and age on the response of the heart to acute ischemia/ reperfusion injury.…”
Section: Diabetesmentioning
confidence: 99%
“…Miki et al (2009) reported that the presence of augmented endoplasmic reticulum stress in the diabetic heart blocked ERK1/2-mediated phosphorylation of GSK-3b, leading to increased susceptibility to MPTP opening and mitochondrial calcium overload. Hotta et al (2010) showed that the angiotensin II subtype 1 receptormediated upregulation of calcineurin in the diabetic rat heart interfered with the phosphorylation of Janusactivated kinase 2 and PI3K-Akt signaling, thereby affecting the efficacy of pharmacologic preconditioning. Ajmani et al (2011) provided data implicating caveolin, which was increased in the diabetic heart and interfered with endothelial NO synthase (eNOS) activity, contributing to the inability of the diabetic heart to respond to ischemic preconditioning.…”
Section: Diabetesmentioning
confidence: 99%
“…Infarct size experiments were performed as previously reported [16,39]. In brief, rats were anesthetized as described above and ventilated with a Harvard Model 683 respirator (Harvard Apparatus, South Natick, MA, USA).…”
Section: Infarct Size Experiments In Vivomentioning
confidence: 99%